2020
DOI: 10.1002/jlb.4hi0320-028r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Anthrax lethal toxin-induced, NLRP1-mediated IL-1β release is a neutrophil and PAD4-dependent event

Abstract: Anthrax lethal toxin (LT) is a protease that activates the NLRP1b inflammasome sensor in certain rodent strains. Unlike better‐studied sensors, relatively little is known about the priming requirements for NLRP1b. In this study, we investigate the rapid and striking priming‐independent LT‐induced release of IL‐1β in mice within hours of toxin challenge. We find IL‐1β release to be a NLRP1b‐ and caspase‐1‐dependent, NLRP3 and caspase‐11‐independent event that requires both neutrophils and peptidyl arginine deim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…In this issue, Greaney et al. demonstrate that neutrophils and peptidyl arginine deiminase 4 (PAD4)‐dependent event are critical for LT‐induced IL‐1β production in vivo 7 . In addition, Greaney et al.…”
Section: Figurementioning
confidence: 98%
See 4 more Smart Citations
“…In this issue, Greaney et al. demonstrate that neutrophils and peptidyl arginine deiminase 4 (PAD4)‐dependent event are critical for LT‐induced IL‐1β production in vivo 7 . In addition, Greaney et al.…”
Section: Figurementioning
confidence: 98%
“…In addition, Greaney et al. also showed that cell‐free DNA are required for LT‐induced IL‐1β production in vivo 7 . Interestingly, LT treatment could not induce IL‐1β production by neutrophil in vitro, and DNA sensing absent in melanoma 2 (AIM2) sensors were dispensable for LT‐induced IL‐1β in vivo, highlighting the complexity of LT‐induced immune responses in vivo.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations